Peer to Peer Interaction Patterns for Mental Health and Student Learning Motivation - Aqillah, Hawwa Nasywa; Laurenza, Audesty Anggraeny; Rosida, Hilda (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This study aims to analyze the pattern of peer interaction in relation to mental health and learning motivation of students at Pondok Pesantren Daar el Syahid, Teluknaga, Tangerang. Peers are an important factor in shaping students' academic behavior and psychological well-being in the pesantren environment, where social interactions take place intensively and continuously. This research used a qualitative method with a case study approach, involving observation, in-depth interviews, and documentation to collect data. Data analysis was conducted through reduction techniques, data presentation, and conclusion drawing. The results showed that peer interaction has a significant impact on students' mental health and learning motivation. Peers act as internal motivators through direct encouragement, positive behavioral examples, and healthy competition. Emotional encouragement from peers is proven to help students cope with academic pressure, while positive behavioral role models encourage students to adopt better study habits. In addition, healthy competition among peers increases students' intrinsic motivation to achieve academically. However, negative social pressure from peers can also impair mental health and decrease motivation to learn. This study concludes that peer interaction patterns at Pondok Pesantren Daar el Syahid play an important role in supporting the balance between students' mental health and learning motivation. Therefore, more structured efforts are needed to encourage healthy and supportive interactions among students as part of efforts to improve their academic performance and psychological well-being.